An empirical study on the impacts of industry effect and macroeconomic conditions on corporate cash holdings: Evidence from UK firms - WANG, ZHENQIAN (2015)
After the 2008 financial crisis, people have become aware of how crucial the role played by corporate cash holdings in financial decision of firms. Numerous previous studies investigate the effects of firm characteristics on cash holdings in recent years, but the impact of industry effect and macroeconomic conditions only receive little attention in this field. This study aims to investigate the impacts of industry effect and macroeconomic conditions on corporate cash holdings by examining 335 UK public firms listed on FTSE all shares index during the period of 2003 and 2012. By using pooled OLS regression model, Fama and MacBeth cross-sectional regression model, and fixed effects regression model, the result shows that the impacts of firm characteristics are generally consistent with the previous studies. Moreover, macroeconomic variable such as GDP growth rate and inflation affect corporate cash holdings. Furthermore, the impacts of firm characteristic and macroeconomic determinants are different across different industry.